Pelayanan Edukasi Kesehatan untuk Mencegah Hiperkolesterolemia pada Santri Pondok Pesantren Tahfidz Al Qur’an H.Nur.Abdullah - Mevy Trisna; Renatalia Fika; Ainun Naim; Muhajri Agusfina; Zul Efendi (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
This Community Service Program is entitled "Health Education Services to Prevent Hypercholesterolemia in Students at the H. Nur Abdullah Al-Qur'an Memorization Islamic Boarding School." Hypercholesterolemia is a medical condition characterized by high blood cholesterol levels, which can increase the risk of heart disease and stroke. This disease can be prevented and managed with lifestyle changes and appropriate medication. The goal of this Community Service Program is to increase students' awareness and knowledge of hypercholesterolemia and provide education on effective prevention and management methods. This Community Service Program is conducted through health counseling, health checks, and education on healthy lifestyles. The target students in this study were students from the H. Nur Abdullah Al-Qur'an Memorization Islamic Boarding School. Prior to the counseling session, 50 students were given a pre-test questionnaire regarding their knowledge of hypercholesterolemia. After the counseling session, a post-test questionnaire on hypercholesterolemia was administered, which showed an increase in knowledge, as evidenced by the post-test results. Following the counseling and health examinations, the students targeted in this study, from the Nur Abdullah Al- Quran memorization Islamic boarding school, showed increased awareness and knowledge about hypercholesterolemia. Most participants also demonstrated healthier lifestyle changes, such as increasing fruit and vegetable consumption and engaging in regular physical activity. This Community Service Program (PKM) demonstrates that health education and counseling can increase the awareness and knowledge of hypercholesterolemia among the students targeted in this study, from the Nur Abdullah Al-Quran memorization Islamic boarding school. Therefore, the students targeted in this community service session, from the Nur Abdullah Al-Quran memorization Islamic boarding school, can effectively implement prev ention and management strategies to reduce the risk of heart disease and stroke.